Agricultural ethics of biofuels: big science and global climate ethics - Thompson, Paul Banks (Journal of global ethics, 2024)
In the first decade of the twenty-first century, biofuels were recognized as an important element in the overall strategy to reduce climate-forcing greenhouse gases, especially carbon dioxide. Yet scientific research to more fully realize the potential of agricultural crops for liquid transportation fuel requires the coordination of many separate projects housed in different disciplines. Studies predicting and documenting adverse social impacts of plant-based ethanol and biodiesel led to the inclusion of social science components within research teams seeking to develop biofuels. A 2008 rise in global food prices became a centerpiece of this research, leading to a search for non-food crops that could serve as energy feedstocks. Although coordinated scientific research teams have made significant strides toward incorporating social dimensions and broader impacts into what was originally a purely biophysical research effort, a simplistic diagnosis of the tension between agricultural production for food use and agricultural production intended for energy production continues to prevail. Some of the hard questions in the global development of the agricultural sector have been obscured as a result.